A Case Report of Puffer Fish Poisoning in Singapore - Y. S. Yong; L. S. Quek; E. K. Lim; A. Ngo (Case Reports in Medicine)
Although many Asians regard puffer fish as a delicacy since ancient times, puffer fish (Lageocephalus scitalleratus) is also a well-known source of possibly lethal food poisoning. The fish is gaining popularity in Singapore and can be found in quite a few restaurants now. Puffer fish contains tetrodotoxin (TTX), a potent poison affecting the neural pathway. Puffer fish poisoning may cause a constellation of symptoms, such as giddiness, numbness and tingling sensation of the mouth, paresthesia, and muscle weakness. Severe cases may present with respiratory depression, circulatory failure, and death. TTX poisonings have been reported in Japan, Taiwan, Hong Kong, Bangladesh, and the United States (Haque et al. 2008). We report a case of mild poisoning and suggest observation for such cases.